Search for gas accretion imprints in voids: II. The galaxy Ark 18 as a result of a dwarf-dwarf merger - Egorova, Evgeniya; Egorov, Oleg; Moiseev, Alexei V; Saburova, Anna S; Grishin, Kirill A; Chilingarian, Igor V (Monthly notices of the Royal Astronomical Society, 2021)
The low-mass low-surface brightness (LSB) disc galaxy Arakelian 18 (Ark 18) resides in the Eridanus void and because of its isolation represents an ideal case to study the formation and evolution mechanisms of such a galaxy type. Its complex structure consists of an extended blue LSB disc and a bright central elliptically shaped part hosting a massive off-centred star-forming clump. We present the in-depth study of Ark 18 based on observations with the SCORPIO-2 long-slit spectrograph and a scanning Fabry-Perot interferometer at the Russian 6-m telescope complemented by archival multiwavelength images and SDSS spectra. Ark 18 appears to be a dark matter dominated gas-rich galaxy without a radial metallicity gradient. The observed velocity field of the ionized gas is well described by two circularly rotating components moderately inclined with respect to each other and a possible warp in the outer disc. We estimated the age of young stellar population in the galaxy centre to be ∼140 Myr, while the brightest star-forming clump appears to be much younger. We conclude that the LSB disc is likely the result of a dwarf-dwarf merger with a stellar mass ratio of the components at least ∼5:1 that occurred earlier than 300 Myr ago. The brightest star-forming clump was likely formed later by accretion of a gas cloud.